Rabbits : a novel - Miles, Terry (Del Rey, 2021)
"Conspiracies abound in this surreal and yet all-too-real technothriller, detailing an underground alternate reality game, set in the same world as the popular Rabbits podcast. Rabbits is a secret, dangerous, and occasionally fatal underground alternate reality game, where the prizes are unclear but may involve vast sums of money, NSA or CIA recruitment, or perhaps even the key to unlocking the secrets of the universe itself. Since the game first started in 1959, ten iterations have appeared and nine winners have been declared. No one knows the true identity of these winners--just their now-famous user names. And everyone is waiting for the eleventh round to begin. K is an expert on the game, although he's never played it himself. He runs information sessions for amateurs at an historic, grungy arcade. But when he is approached by billionaire Alan Scarpio--the alleged winner of the sixth iteration--his world is turned upside down. Because Scarpio wants his help fixing the game, which he claims has become corrupted. And if the eleventh iteration begins before the game is repaired, he claims, all hell will break loose. Soon K is in way over his head, chasing down a myserious rabbit hole that is getting stranger and twistier and more perilous by the day. Because, as it happens, he blows the deadline, Eleven begins...and suddenly there is far more than just his own life at risk..."--